Parliaments as Peacebuilders in Conflict-Affected Countries - O'Brien, Mitchell; Stapenhurst, Rick; Johnston, Niall (2012)
The role of parliament in conflict-affected countries becomes even more evident when the correlation between poverty and conflict is considered. This book is pioneering in that it considers what parliaments in conflict-affected countries can do, while performing their normal everyday functions, to not only contribute directly to conflict prevention but also aid peace building by combating poverty. By addressing issues of poverty, equitable distribution of resources, and economic development, parliamentarians can attempt to guard against the creation of an enabling environment that is prone to the escalation of conflict. In line with their respective missions, the World Bank Institute and the Commonwealth Parliamentary Association have examined issues facing parliamentary development in the hope of strengthening parliaments' capacity to tackle the diverse challenges they face. Among those challenges is meeting growing community expectations of the contribution parliaments make to resolving important issues and addressing community demands. In recognition of the rising number of parliaments that are operating in conflict-affected societies, the World Bank Institute has sought to better understand the challenges faced by parliaments in conflict-affected countries and the role parliaments can play in conflict management and poverty alleviation.